International football players with cerebral palsy maintained their physical fitness after a self-training program during the COVID-19 lockdown - Peña-González,Iván; Sarabia,José Manuel; Manresa-Rocamora,Agustín; Moya-Ramón,Manuel (PeerJ, 2022)
Background The COVID-19 global pandemic caused a complete stop in sport participation which meant a detraining period for athletes. High-level athletes had to train at home guided by their coaches and conditioning trainers in an effort to maintain their physical fitness. The aim of maintaining the training adaptations and physical fitness during the COVID-19 mandatory lockdown was especially important for CP athletes, in which the detraining period was expected to cause early declines in motor function, poor coordination and muscle weakness due to their disability. Methods The present study assessed the effect of a guided self-training program on international CP football players’ physical fitness during the COVID-19 mandatory lockdown. Fifteen CP football players from the Spanish National Team participated in the study. An experimental design with a pre- (T1) and a post-intervention (T2) assessment was carried out, with a 12-week period of players’ self-training (divided in two periods of 6 weeks) which combined strength and endurance training. Physical performance assessment consisted in the free countermovement jump (CMJ), 5, 10 and 20-m sprint, the modified agility T-test (MAT) and a dribbling test. The Kruskal–Wallis test was used for between-group comparisons, while the Student’s paired t test or the Fisher Pitman permutation test, based on the normality of the data, were used for within-group comparisons. Results The results showed no differences between sport classes (FT1, FT2 and FT3) in physical fitness change after the training program (Chi2 = 0.16 to 1.73; p = 0.42 to 0.92). Within-group comparisons showed an increase of jump height in the CMJ (4.19 cm [2.46, 5.93]; p < 0.001) and a maintenance of the 5, 10 and 20-m sprint, MAT and dribbling ability (<0.01 to 0.09 s; p = 0.19 to 0.97). Discussion To the authors’ knowledge, this is the first study that examined the physical fitness adaptations to a training program with CP football players. The results show that a 12-week guided self-training program without football-specific stimulus may be effective to maintain or even improve the specific physical performance of international CP football players during a non-competitive period (as the COVID-19 lockdown). This study reveals that CP football players are able to show adaptations to the strength and endurance training and this could be the basis for future research regarding training adaptations in CP football players.
Keywords: CP football; Physical performance; Training; Sport; Disability